Antrodia cinnamomea mycelial fermentation broth inhibits the epithelial-mesenchymal transition of human esophageal adenocarcinoma cancer cells. (September 2018) - Liu, Yu-Ming; Liu, Yu-Kuo; Huang, Pin-I.; Tsai, Tung-Hu; Chen, Yu-Jen
Abstract: Esophageal cancer is associated with a high mortality rate and easy metastasis. The aim of this study is to investigate the effect of the bio-product Antrodia cinnamomea mycelial fermentation broth ( AC -MFB) on the epithelial mesenchymal transition (EMT) of human esophageal cancer cells and the molecular mechanisms underlying these effects. Transforming growth factor β (TGF-β) was used to induce EMT in human esophageal BE3 cancer cells. Changes in cell morphology and migration potential were examined. The expression of E-cadherin, N-cadherin, vimentin, and other transcriptional factors was studied by western blot assay. The results showed that AC -MFB was not only able to upregulate the expression of Ecadherin and attenuate the TGF-β-induced overexpression of vimentin and N-cadherin, but it also reversed the TGF-β-induced changes in cell morphology from polygonal to spindle-shaped and delayed the migration potential of BE3 cells. Furthermore, AC -MFB treatment was able to inhibit the expression levels of both Twist and Twist1. Overall, AC -MFB was able to inhibit the EMT of esophageal cancer BE3 cells, which was accompanied by Twist and Twist1 downregulation. Highlights: Esophageal cancer is associated with characters of EMT as easily metastasis and high mortality rates. AC -MFB, a biotechnologically product, from Antrodia cinnamomea . AC -MFB treatment could attenuate cellular migration, inhibit the TGF-β induce overexpression of Vimentin; reverse the E-cadherin to N-cadherin switch in esophageal cancer BE3 cells. The pathways of AC -MFB inhibit the EMT of BE3 cancer cells might be through Twist and Twist1 downregulation.